MANAJEMEN STRATEGIS KAMPUNG 3G (GLINTUNG GO GREEN) , BLIMBING, MALANG, DARI LOKAL MENUJU GLOBAL - Erlin Iriani (Akubis : Jurnal Akuntansi dan Bisnis, 2020)
Kampung 3G once popular as a slum area, the area alwaysflooded in the rainy season, in the other hand the citizen wereapathetic, lazy, and less care (of the environment). Five yearslater it have changed to a free-flooded area, the environmentbecomes beautiful, cool, and cozy. The citizen character of thekampung also changed to optimist, hardworker, and careabout their environment. This condition attract me doing theresearch. I used deep intervew method for Kampung 3G’smanagement to collect the data.The changes of their characters upgrade their income,because the slum areas of Kampung 3G already changed to aneducational vacation kampung. The micro-small-mediumbusiness popping up, ranging from hydroponic plants,hydroponics media, compost, spice drinks, to homestays.Some of Kampung 3G programs becomes a reference for otherarea, for example Gemar (Gerakan Menabung Air or WaterSaving Movement), and urban farming. Many awardsachieved, from the city, province, up to national andinternational level.Implementing the policies strickly by giving punisment to thecitizen who broke the policies is the succes key to change thebad behaviour. The citizen must build inovasion and up gradethe creativity to enhance Kampung 3G as an educationalvacation kampung longer.